The Effect of English Courses on Students’ English Learning at SMAN 3 Gowa - Almira, Nisa; Noni, Nurdin; Korompot, Chairil Anwar (State University of Makassar, 2025)
This research highlights the effect of English courses on English learning to find out (1) the difference in achievement or achievement of students who take courses and students who do not take courses, and (2) the difference in English language performance of students who take courses and students who do not take courses. This research uses mixed methods by taking a sample of 30 students of class XII SMAN 3 Gowa using a purposive sampling technique. The instruments used were documentation, observation, and interview. Thirty students as representatives of documentation, namely the English report card scores of odd semester students of class XII, fifteen students as representatives of students who take courses, and students who do not take courses were observed and interviewed regarding how the difference in English performance of students who take courses and students who did not take courses. 30 students were selected, 15 students were selected because they take English courses and 15 students were selected who did not take English courses. This method used criteria that have been chosen by the researcher in selecting samples, namely inclusion criteria where the inclusion criteria are the sample criteria that the researcher wants based on the research objectives with various criteria such as students who have fairly high scores and not very high scores such as 87, 88, 89 in English subjects. This was tested using an SPSS version 22 independent t-test to determine whether there is an effect of the course on English learning. The researcher obtained a significant result of 0.049 < 0.05 which means that there is a difference in achievement between the students who take English courses and those who do not take English courses on student English learning at SMAN 3 Gowa.Keywords: English course, English learning